BASIC MECHANISM OF HYPERBARIC OXYGEN IN INFECTIOUS DISEASE - Widiyanti, Prihartini (Institute of Topical Disease, 2011)
Hyperbaric oxygen therapy (HBOT) is the inhalation of 100 percent oxygen inside a hyperbaric chamber that is pressurized to greater than 1 atmosphere (atm). HBOT causes both mechanical and physiologic effects by inducing a state of increased pressure and hyperoxia. HBOT is typically administered at 1 to 3 atm. While the duration of an HBOT session is typically 90 to 120 minutes, the duration, frequency, and cumulative number of sessions have not been standardized. HBO has been use widely in treating gangrene diabetic, stroke, osteomyelitis and accelerating wound healing. The use of HBO in infectious disease is wide, so the mechanism of hyperbaric oxygen in infectious disease should be well-understand. This understanding could bring the proper and wise management of infectious disease and to prevent the side effect of each therapy.